Racial/Ethnic and Educational Disparities in the Impact of Diabetes on Population Health Among the U.S.-Born Population. (10th August 2021) - Zang, Emma; Lynch, Scott M; Liu, Chen; Lu, Nancy; Banas, Julia
Abstract: Objectives: This study examines total life expectancies (TLEs) for both healthy and diabetic U.S.-born populations and 2 measures capturing quality of life: (a) the proportion of remaining life to be spent without either other chronic conditions or activities of daily living disabilities (ADLs) and (b) the proportion of remaining life to be spent with ADLs for U.S.-born diabetic populations by race/ethnicity and educational attainment. Methods: Using the 1998–2014 waves of the Health and Retirement Study ( n = 16, 983), we apply a Bayesian multistate life table method to calculate these quantities from the constructed life tables. Results: TLE at age 50 is shorter for diabetic individuals than healthy individuals, for non-Hispanic Blacks than members of other racial/ethnic groups, and for less-educated individuals. Gaps in TLE at age 50 between healthy and diabetic populations range from 6.3 to 8.8 years across sex–race combinations and from 5.6 to 9.2 years across sex–education combinations. Among the diabetic population, those with at least a college degree on average have a higher proportion of remaining life to be spent without either other chronic conditions or ADLs. Hispanics and those without a college degree have a particularly high proportion of remaining life to be spent with ADLs. Although diabetic women on average live longer than men, their quality of life tends to be lower. Discussion: The impact of diabetes on population health varies across racial/ethnic and educational groups. The findings support targeted interventions for vulnerable groups, such as people of color, women, and less-educated individuals.